The effect of stevia, emulsifier and milk powder on melting rate, hardness and overrun of ice cream formulations during storage - Sulejmani, Erhan (Array, 2020)
Four types of ice creams were manufactured using stevia (S), milk powder (PP), emulsifier (PS) and UHT whole milk (C), and were investigated for physical, chemical and sensory characteristics. The pH values of ice cream samples ranged from 5.82 to 6.62. The hardness values from textural analyses was around 3.40 and 598.61 N. The highest overrun ratio (29.27 %) was found in PP ice cream during the first week of storage. The substitution of sucrose by stevia powder led to a significant elevation of the hardness of ice cream.